Immobilization of cyclodextrin glucanotransferase on polyvinylidene fluoride hollow fiber membrane for cyclodextrin production - Natassha, Jamil (2019)
Cyclodextrin glucanotransferase (CGTase) is a multifunctional industrial enzyme that undergoes cyclization reaction to converts starch into cyclodextrin (CD). CD is a non-reducing maltooligosaccharides with a hydrophobic inside and hydrophilic surface outside. With these properties, CD able to form inclusion complexes with many hydrophobic molecules, changing their physical and chemical properties. Due to their potential properties, CD has been discovered to have numerous application in food industries, pharmaceutical, agricultural and environmental engineering. However, the instability of the enzyme during the reaction process resulted in the low production of CD. Therefore, enzyme immobilization technique is a promising solution to improve the enzyme stability in order to achieve high production of CD. The aims of this study are to optimize the immobilization of CGTase on polyvinylidene fluoride (PVDF) hollow fiber membrane by manipulating the immobilization parameters and to investigate the performance of the immobilized enzyme compared to the free CGTase on CD production. In the present study, one-factor-at-one-time (OFAT), fractional factorial design (FFD) and central composite design (CCD) were employed to screen and optimize the effect of immobilization conditions towards the immobilization yields. The reusability and kinetic study of the immobilized enzyme were also performed in order to study the performance of the immobilized CGTase. The free CGTase from Bacillus licheniformis was characterized to determine their optimum temperature and pH for CD production. The enzymatic activity was highest at the temperature of 40 °C and pH 6.0. Immobilization of CGTase on the PVDF hollow fiber membrane was successfully performed via adsorption technique. The effects of enzyme concentration, temperature, agitation rate, contact time and pH on the enzyme immobilization yield were investigated by OFAT method. The immobilized CGTase exhibited an immobilization yield of 19.21% under the conditions of 100 U of enzyme concentration, 25 °C of immobilization temperature, 100 rpm of agitation rate, 24 h contact time and pH 4.0. The immobilization of CGTase on hollow fiber membrane was further optimized by using response surface methodology (RSM). Under the optimized conditions [100 U of enzyme concentration, 24 °C of immobilization temperature, 100 rpm of agitation, 24 h of contact time and pH 6.7], 88.25% of CGTase immobilization yield was recorded. This illustrated that 4.6-fold increment of the immobilization yield was achieved compared to before optimization process. The reusability of the immobilized CGTase revealed that the immobilized enzyme could retain 37.7% of its initial activity after 10 cycles of reusability. The cumulative production of CD by the immobilized CGTase after 10 cycles was 26.43 mg/ml. The kinetic study of the immobilized and free CGTase discovered that the immobilization process not relatively altered the intrinsic characteristic of the enzyme, suggesting that the hollow fiber membrane appeared as a suitable support for enzyme immobilization system. Hence, immobilization of CGTase on the hollow fiber membrane substantially improved the production of CD by allowing the reusability of the enzyme.